2019
DOI: 10.1021/acs.chemmater.8b04769
|View full text |Cite
|
Sign up to set email alerts
|

CuGaS2–CuInE2 (E = S, Se) Colloidal Nanorod Heterostructures

Abstract: Colloidal nanorod heterostructures of I–III–VI2 semiconductors have been synthesized in a solution starting from wurtzite-like CuGaS2 nanorods. Growth of CuInS2 or CuInSe2 on CuGaS2 nanorods results in interesting sawtooth structures with larger lattice strain leading to sharper, more pronounced teeth. A final inorganic shell of ZnSe or ZnS grown on the CuGaS2/CuInSe2 nanorod heterostructures enhances photoluminescence. Unusual brush-like structures arise with prolonged ZnSe growth. Time-resolved photoluminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 56 publications
(88 reference statements)
0
22
0
Order By: Relevance
“…Ultraviolet-visible spectroscopy (UV-Vis), photoluminescence spectroscopy (PL), and X-ray diffraction (XRD) of ~ 100 nm CuGaS 2 NRs produced via this procedure have been reported in a previous work. 26 At the beginning of the synthesis, Cu 2-X S nanocrystals nucleate and grow but quickly convert to what appears to be a relatively monodisperse collection of Cu 2-X S/CuGaS 2 Janus particles (Fig. 1a).…”
Section: Synthesis Of Cugas 2 Nrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultraviolet-visible spectroscopy (UV-Vis), photoluminescence spectroscopy (PL), and X-ray diffraction (XRD) of ~ 100 nm CuGaS 2 NRs produced via this procedure have been reported in a previous work. 26 At the beginning of the synthesis, Cu 2-X S nanocrystals nucleate and grow but quickly convert to what appears to be a relatively monodisperse collection of Cu 2-X S/CuGaS 2 Janus particles (Fig. 1a).…”
Section: Synthesis Of Cugas 2 Nrsmentioning
confidence: 99%
“…However, as shown here and in our prior investigation by HRTEM, SAED, and XRD, the CuGaS 2 NRs are wurtzite-like throughout. 26 We then expect the surface termination of the CuGaS 2 NR to be the primary determining factor in the nucleation of CuInE 2 . The expected surface termination for a section of CuGaS 2 rod with <0001> growth direction is {10 0} with an overall hexagonal 1 shape.…”
Section: Regioselective Heterostructure Nucleationmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, accumulating evidences demonstrate that copperbased ternary I-III-VI 2 (I ¼ Cu; III ¼ Ga, In; VI ¼ S, Se, Te) chalcogenide semiconductor materials have received a great deal of attention due to their distinct composition and structure-tunable properties and extensive applications. [21][22][23][24][25][26][27][28][29][30][31] For instance, Wang et al reported a hot injection method for the preparation of monodispersed wurtzite structure CuInSe 2 nanocrystals with uniform hexagonal shape as well as their high performance in optoelectronic application. 32 Xia et al demonstrated a solvothermal synthesis technique to prepare CuInS 2 quantum dots and studied their size-dependent optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal nanocrystals (NCs) have gained great emphasis in both fundamental science and technological aspects due to their compositional diversity and easily tunable size, shape, and morphology, which give rise to an interesting optical, electronic, magnetic, and catalytic activity. Among those, nanoscale heterostructures (NHSs) with different chemical domains have attracted much greater attention from researchers as they possess new functionalities and applications. NHSs, in particular, semiconductor–semiconductor heterostructures, are widely explored because of their huge variety in chemical composition, size, shape, and crystalline structure. These heterostructures offer exciting possibilities regarding band engineering, which allows spatial charge separation between two different nanomaterials. From the fundamental point of view, type-I band alignment gives localization of charge carriers into a particular semiconductor domain; whereas in type-II band alignment, electrons and holes are localized at two different domains.…”
Section: Introductionmentioning
confidence: 99%